Teacher Strategies for Overcoming Students' Difficulties in Learning Arabic Vocabulary at Al-Hikma Islamic Primary School in Bintaro - Azmy Ali Muchtar; Farah Nursaidah; Muhammad Qadhafi (Al-Muyassar: Journal of Arabic Education, 2026)
This study aims to determine the teacher's strategy in overcoming students' learning difficulties in learning Arabic vocabulary at SDIT Al-Hikmah Bintara. Students' difficulties in understanding, memorizing, and applying Arabic vocabulary are caused by internal and external factors, such as the lack of variety in teaching methods, low student motivation, and the lack of use of interactive learning media. This study used descriptive qualitative method with observation, interview, and documentation techniques. The results showed that most students had difficulty in memorizing long vocabulary, understanding the meaning of words, and reading in Arabic. To overcome this problem, teachers apply the talaqqi method, the use of songs and poems, as well as interactive quizzes and games. In addition, teachers utilize visual media such as videos and pictures to clarify the meaning of vocabulary and repeat the material regularly to improve student retention. With the application of innovative and effective strategies, students are expected to understand and memorize Arabic vocabulary more easily, thus improving their language skills.